الأغاني التلفزيونية المصورة ومظاهر العولمة الثقافية: دراسة تحليلية لعينة من الأغاني المصورة في الفضائيات العربية - سحنون، نصيرة (مركز فكر للدراسات والتطوير, 2022)
تهدف هذه الدراسة إلى الكشف عن مظاهر العولمة الثقافية المتضمنة في الأغاني المصورة التي تبثها قناة روتانا الغنائية، حيث حاولنا البحث في الكيفية التي تعمل بها هذه الأغاني للترويج للعولمة الثقافية التي أصبحت من القضايا المثيرة للجدل في المجتمعات ذات الخصوصية الثقافية مثل المجتمع العربي. وقد أجرينا الدراسة استنادا إلى المنهج الوصفي واحتكمنا إلى أداة جمع البيانات المتمثلة في تحليل عينة من الفيديو كليبات عرضتها القناة مؤخرا وتم اختيارها بطريقة قصدية بما يتماشى مع الهدف من الدراسة. وتوصلنا إلى نتائج جوهرية أهمها أن الأغاني العربية المصورة كنسق ثقافي ووعاء إعلامي يغيب فيها المعنى وغارقة في التقليد. لكنها قادرة بامتياز على نقل العولمة الثقافية كونها تضمنت جملة واسعة من مظاهر هذه العولمة بتأكيدها على نمط العيش الغربي القائم على الاستهلاك المادي وتسويق المرأة كجسد أنثوي محرك للشهوات، مع تقديم صورة مشوهة ومضللة عن الواقع وتعزيز مظاهر التغريب داخل المجتمع العربي مما ساعد على تهميش ثقافته المحلية والمتنوعة. This study aims to identify the aspects of cultural globalization embodied in the video songs broadcast by the Rotana channel. This paper seeks to recognize the way these songs work to promote cultural globalization, which has become one of the controversial issues in societies with cultural specificity such as the Arab society. To doing so, this piece of research is carried out based on the descriptive approach, as it also used the data collection tool, which is to analyze a sample of video clips the channel recently presented. The video clips were chosen intentionally in line with the objective of the study. The most important findings of this study are: that the Arab songs represented as a cultural system and a media container, lack meaning and are mired in traditional slander. However, they are perfectly capable of transmitting cultural globalization, as they include a wide range of its manifestations by emphasizing the Western lifestyle, based on material consumption and the marketing of women as a female body that drives lusts. They also present a distorted and misleading picture of reality and promote manifestations of destruction within the Arab society; things that helps marginalizing its local and diverse culture.
Keywords: تكنولوجيا المعلومات -- الثورة الرقمية -- الانفتاح المعرفي -- الموسيقى التلفزيونية -- الثقافة الإعلامية